UNBALANCED NUTRITION AS A FACTOR CAUSING DISRUPTIONS IN THE MENSTRUAL CYCLE AND OVARIAN FUNCTION IN YOUNG WOMEN INVOLVED IN BODYBUILDING - Safronova M.Y.; Tambovtseva R.V. (Theory and Practice of Physical Culture, 2025)
Objective of the study is to identify the relationship between nutritional deficiencies in female athletes specializing in bodybuilding and disorders of their ovarian-menstrual cycle (OMC). Methods and structure of the study. A rational method for reducing caloric intake by reducing fat intake was developed and a survey of girls specializing in bodybuilding was conducted. Results and conclusions. It was found that disorders (absence) of the OMC mainly occur due to a decrease in carbohydrates and fats to a critical level. The worst effect on the ovarian-menstrual cycle is a decrease in the percentage of fat in the diet to 10-15%. Those girls who maintained their OMC followed a diet containing 30-35% fat.